Foreign direct investment inflows in Malaysia: a quantitative approach / Nur Liyana Mohamed Yousop ... [et al.] - Mohamed Yousop, Nur Liyana; Azman Ong, Nurhafiza; Ramdhan, Nur'Asyiqin; Ahmad, Zuraidah; Mohd Hasan Abdullah, Norhasniza; Nasrul, Ferri; Md Kamdari, Nor' Azurah; Azman Ong, Mohd Hanafi (2018)
This study had been conducted due to realizing the importance of FDI inflows. After considering previous studies, this study aims to (1) examine the relationship between FDI inflows in Malaysia and the macroeconomic variables (gross domestic product (GDP), inflation (INF), trade openness (TRO), exchange rate (ERT), government consumption expenditure (GSE)) and (2) to determine the main macroeconomic variables that affect FDI inflow in Malaysia. The data for the macroeconomic variables were obtained through World Bank Data and the data sampling was drawn from 37 years' time series data (1980 until 2016). Based on the findings that were analyzed using multiple linear regression and time-series approach, this study found that there is a positive relationship between FDI inflows and the two macroeconomic variables which are GDP and INF. While the three other macroeconomic variables (TRO, ERT, and GSE) have not shown any significant relationship towards FDI. Future researchers are suggested to provide different models in order to investigate FDI inflows in Malaysia. The model used in this study could provide evidence on a relationship between FDI inflows and the macroeconomic variables.